KARAKTERISTIK PRODUKSI DAN MUTU LADA LOKAL KALIMANTAN TIMUR - Otih Rostiana; Dyah Manohara; Agus Ruhnayat; NFN Wiratno (Pusat Penelitian dan Pengembangan Perkebunan, 2017)
East Kalimantan is one of production center for white blackpepper, known as Samarinda White Pepper products. The variety developed in East Kalimantan is a local blackpepper variety that is not yet known for its characteristics. The research was conducted to observe the production and quality of local blackpepper in East Kalimantan, specifically in Kutai Kartanegara Regency which is the widest blackpepper development area in East Kalimantan. The observation was conducted for two years, at three locations of high yielding block (BPT) in Loa Janan and one non-BPT location in Muara Badak, as a local origin of local East Kalimantan blackpepper which is currently developing in Loa Janan. The environmental design used was a Randomized Block Design, with four trial sites, repeated six times in each location, using the same variety (local blackpepper). The average production for two years of observation reached 2.94 kg fresh berries/tree equivalent to 2.17 tons of white pepper/ha/year. However, the average of spikes containing pepper berries reached only 61.3% per panicle. Therefore, it requires intensive fertilization with appropriate dosage and fertilizer type to increase the expression of its potential genetic because local pepper of East Kalimantan bears fruit continuously throughout the year. Result of yield-quality analysis showed that local white pepper of East Kalimantan contained 11.23% oleoresin and 3.82% piperin, higher than Petaling 1 (10.66% and 3.03%, respectively). The superiority characteristics of local blackpepper of East Kalimantan is a distinctive aroma and spicy flavor, due to the high content of piperin and oleoresin.